The Effect of Government Subsidies-in-Kind on Private Expenditures: The Case of Higher Education - Peltzman, Sam (Journal of Political Economy, 1973)
The article points out that a subsidy-in-kind, such as below-cost education provided by state universities, replaces more private consumption of the subsidized good that an equivalent money subsidy, such as a scholarship. Indeed, a subsidy-in-kind may reduce total consumption. Empirical estimates in the article indicate that in higher education (a) about three-fourths of government expenditures substitute for private expenditures, (b) this fraction has exceeded one in a recent period, (c) a substantial part of this government-private substitution is due to the in-kind form of government subsidies, and (d) there is less government-private substitution in enrollment than expenditures.